KETERPAKAIAN KONSEP HUKUM BERNOULLI DAN DESAIN EKSPERIMENNYA DI DALAM FISIKA TERAPAN PRODI REKAYASA POLBAN - I Gede Rasagama; Ratu Fenny Muldiani; Kunlestiowati Hadiningrum (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The study aim is to determine the usefulness of the concept and design of experiments Bernoulli's Law in Proficiency Basic Courses (PBC) of Applied Physics at the Polytechnic. The place of research is in POLBAN. The study begins review of PBC syllabus of Applied Physics and Prodi Proficiency Courses (PPC) syllabus at the Department of Engineering, who gets service PBC of Applied Physics. Continued with questionnaire to lecturers PPC is 3 DIII and 3 DIV. To deepen the contents of the questionnaire, we conducted interviews to informants. Data were analyzed to measure: usefulness of Bernoulli's Law concepts in the PBC of applied physics and PPC syllabus, PPC lecturer opinion about needs of Bernoulli's Law concept in PBC of Applied Physics, the necessity of deepening through experiments and experimental design characteristics. The study results showed 11 prodi of 24 prodi in engineering majors, inserts the concept of Bernoulli's Law into the applied physics syllabus, all research subjects insert the concept of Bernoulli's Law in the one of PPC syllabus, overall interviewees believe it is needed to be taught the concept of Bernoulli's Law in PBC of Applied Physics, and 67% informants believe it is necessary for deepening through experimentation. Characteristic of the expected experimental design is capable of generating student competence in measuring the speed and pressure of the flow in the pipes of various sizes. The ideal approach, requirement, and limits of the enforceability of Bernoulli's Law can be used as the basis of design of experiments. It appears that the usefulness category of Bernoulli's Law concept for students and polytechnic institutions is high Keywords: Bernoulli’s Law, experimental design, polytechnics students applied physics.